2009
DOI: 10.1007/s00701-009-0248-y
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of human brain tumor tissue by near-infrared laser coherence tomography

Abstract: IntroductionIntraoperative detection of residual tumor remains an important challenge in surgery to treat gliomas. New developments in optical techniques offer non-invasive high-resolution imaging that may integrate well into the workflow of neurosurgical operations. Using an intracranial glioma model, we have recently shown that time domain optical coherence tomography (OCT) allows discrimination of normal brain, diffusely invaded brain tissue, and solid tumor. OCT imaging allowed acquisition of 2D and 3D dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(166 citation statements)
references
References 39 publications
6
158
0
2
Order By: Relevance
“…According to the reference sources, the resolution + between perifocal zone and glioblastoma, p<0.0000003; v between glioblastoma and pilocytic astrocytoma, p<0.000001 capacity of OCT is sufficient to determine the area of tumor infiltration where there are specific changes in the scattering properties compared with healthy brain tissue [28]. Our results showed that visually the signal from glial tumors in the OcT images in co-polarization looks heterogeneous in comparison with the homogeneous signal of the brain tissue from the perifocal zone, and this correlates with the data from other studies [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the reference sources, the resolution + between perifocal zone and glioblastoma, p<0.0000003; v between glioblastoma and pilocytic astrocytoma, p<0.000001 capacity of OCT is sufficient to determine the area of tumor infiltration where there are specific changes in the scattering properties compared with healthy brain tissue [28]. Our results showed that visually the signal from glial tumors in the OcT images in co-polarization looks heterogeneous in comparison with the homogeneous signal of the brain tissue from the perifocal zone, and this correlates with the data from other studies [17].…”
Section: Methodsmentioning
confidence: 99%
“…The spatial resolution of OcT (unlike MPT) cannot provide subcellular visualization and differentiation between benign and malignant brain tumors. Qualitative evaluation of images and the differentiation criteria in this case are based on the intensity and heterogeneity of the OcT signal, and the rate of its attenuation [17,28].…”
Section: No4 65 сLinical Medicinementioning
confidence: 99%
“…Bizheva et al reported the first studies on ex vivo human tissues (65). Böhringer et al reported imaging of human brain tumor specimens using TD-OCT and SD-OCT system to identify tumor and normal tissue using optical characteristics (66)(67)(68). Due to the intrinsic optical property of brain tissue, near-infrared OCT has a deeper viewing field/range than visible light used in the OCT system (42,67-69).…”
Section: Identification Of Tumorous and Non-tumorous Tissue With Oct mentioning
confidence: 99%
“…psoriasis [318]; assessment of arteriosclerotic plaques [319,320]; and determining burn extent and tissue viability by defining tissue barrier layers characteristic of scarring (wound healing and graft flow) [321][322][323]. However, in truth, OCT has ubiquitous applications, having emerged in a variety of clinical fields: ophthalmology [324][325][326], intravascular imaging in cardiology [327,328], oncology [329,330], gastroenterology [331][332][333], general dermatology [334][335][336], dentistry [337,338], and gynaecology [339,340], to name a few. Functional extensions of OCT have emerged: polarisation-sensitive systems used, for example, in the diagnosis of neoplastic 6 processes; differential phase-sensitive methods for use in photorefractive surgery; full-field advancement of the conventional single-point OCT detection technique; and endoscopic OCT.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%